Dinamika Pengungkapan Diri dalam Persahabatan Mahasiswa di Indekos: Analisis Berdasarkan Teori Penetrasi Sosial - Riyadi; Hafied Cangara; Tuti Bahfiarti (Journal of Mandalika Literature, 2025)
Interpersonal relationships are crucial for university students navigating the transition to adulthood, particularly in dormitory settings that blend shared spaces with individual privacy. This study investigates the self-disclosure process among students living in dormitories with separate rooms, utilizing the Social Penetration Theory framework. Adopting a qualitative phenomenological approach, data were gathered through in-depth interviews with 10 informants. The results reveal a gradual progression of interpersonal relationships through four stages: orientation, exploratory affective exchange, full affective exchange, and stability. Each stage is influenced by the dynamics of dormitory life, where shared areas like kitchens and living rooms encourage interaction, while private rooms maintain personal boundaries. The findings align with Social Penetration Theory, demonstrating that self-disclosure evolves from surface-level conversations to deeper emotional exchanges as trust develops. Trust, shared experiences, and consistent interaction are identified as critical factors in fostering closer relationships. These insights emphasize the importance of communal environments in supporting interpersonal growth. The study concludes that while individual privacy is valued, shared spaces play a pivotal role in promoting social bonding among students. Recommendations include designing dormitory layouts to facilitate interaction and implementing university programs to foster a sense of community, especially for students living away from their families. This research contributes to understanding how self -disclosure unfolds within a collective culture and provides practical strategies to enhance student well- being and connection.